2011
DOI: 10.1177/0363546511428580
|View full text |Cite
|
Sign up to set email alerts
|

Does Anterior Cruciate Ligament Reconstruction Lead to Degenerative Disease?

Abstract: At 13 years, BTB ACL reconstruction provides a good outcome. Chondral and meniscal damage at surgery were associated with a poor radiological outcome, indicating that injuries sustained during ACL rupture may be the main predictors of degenerative bone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 43 publications
(56 reference statements)
0
51
0
2
Order By: Relevance
“…To date, there has been no evidence to demonstrate that ACL reconstruction or subsequent revision surgery can prevent OA [91]. In study after study [168,[171][172][173][174], the consensus has been that there is a substantial risk of progression to OA once an ACL injury has been sustained. One study did indicate that ACL reconstruction cannot prevent OA, but may lead to a lower prevalence of its onset and reported that the rate of osteoarthritis progression showed more severe changes in non-reconstructed patients with additional meniscus injury [175].…”
Section: Surgerymentioning
confidence: 99%
“…To date, there has been no evidence to demonstrate that ACL reconstruction or subsequent revision surgery can prevent OA [91]. In study after study [168,[171][172][173][174], the consensus has been that there is a substantial risk of progression to OA once an ACL injury has been sustained. One study did indicate that ACL reconstruction cannot prevent OA, but may lead to a lower prevalence of its onset and reported that the rate of osteoarthritis progression showed more severe changes in non-reconstructed patients with additional meniscus injury [175].…”
Section: Surgerymentioning
confidence: 99%
“…Despite reasonable success of ACL reconstruction, the current gold standard of treatment, in restoring the gross stability of the ACL-deficient knee, it fails to restore normal joint kinematics and kinetics [8,22,24,25,43,52]. Moreover, ACL reconstruction is associated with reduced activity level [5], an increased rate of secondary injury [48], and high risk of posttraumatic osteoarthritis (OA), up to 74%, even with advanced anatomic reconstruction techniques [13,32,33,40,50,56]. The associated complications with ACL reconstruction, in addition to the advent of functional tissue engineering, precipitated a move in ACL research from improving replacement techniques to developing procedures for biologically augmented repair of the ligament.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Se han propuesto distintas técnicas, que difieren entre sí en el tipo de injerto utilizado: hueso-tendón-hueso, tendones isquiotibiales, método de fijación tibial y femoral, ubicación de los túne-les y utilización de portales accesorios, por nombrar las más frecuentes.…”
Section: Discussionunclassified